KAJIAN YURIDIS NORMATIF PENYELENGGARAAN REKAM MEDIS ELEKTRONIK DI FASILITAS KESEHATAN - Ahmad Yani Noor; Nurrul Ainy (Jurnal Infokes, 2021)
The rapid technology development, written documents are increasingly replaced by digital data which has many benefits in their use. In the health sector, several health facilities have tried to switch from manual medical records to electronic medical records. Based on some of the results of existing research, the implementation of electronic medical records has many contradictions, one of the fundamental contradictions regarding the law of the administration and legal strength of electronic medical records. This study was approved to be approved by the juridical medical record at a health facility. The recommendations used in this normative study are statutory regulations and conceptual approaches. Based on the results that have been made, no one has set about electronic medical records. The regulations that underlie there are replacements to organize electronic medical records that are regulated in article 29 Paragraph (1) letter h of Law Number 44 of 2009 concerning Hospitals reported in the annex to the elaboration of the regulation. When the implementation of electronic medical records in several health facilities in Indonesia has been running, but the current regulations cannot yet regulate the implementation of electronic medical records in a holistic manner. Therefore it is necessary to realize a special regulation based on the mandate of article 2 paragraph (2) Permenkes Number 269 of 2008 concerning Medical Records.